Dialect of American and British English Style through Listening Material Analysis : Language Learner’s Perception - Musdalifah Musdalifah (JOEY: Journal of English Ibrahimy, 2022)
This research is based on the problem of the importance in analyzing the materials for teaching, especially in listening courses. In this case, the selection and preparation of teaching learning will be important for learning process by transfering a knowledge to students. It has to always increase to make a new innovation and high quality in teaching learning process. One of its functions is to create the teaching learning atmosphere will be full of variations in learning materials. It means that the materials of teaching should be depend on the needs and also the conditions of the learner. This research was conducted in the listening class at the 2nd semester for listening course of the social and humanities faculty. The subjects in this research were 20 students of the English education department. The material provided in the form of video and audio related to an American dialect and British English Style. The material was presented by watching a kind of video, audio that related with an American and British English style, after that the students try to listen carefully, understand a kind of an accent and dialect of American and also British English style, than finally the students can give their perception of the dialect and accent of American and British style. While the research method of this study is a qualitative method with interview techniques.